Traducción y adaptación de un instrumento para medir actitudes sexuales en migrantes - Benavides Torres, Raquel Alicia (NOVA, 2020)
HIV is a health problem in Latin American countries and in Mexico since there is a high migration to the United States. Due to their vulnerable situation, migrants engage in risky sexual behaviors that put them at risk of HIV infection. Favourable attitudes towards our age significantly associated with sexual behaviour. However, to date there is no Spanish-language instrument that has been contextualized for use with the migrant population, so the aim of this study is to develop a Spanish-language version of an instrument to measure sexual attitudes to humans through the process of translation and cultural adaptation by Chávez and Canino